Lead and zinc contaminated mining tailings filament fungi - Llacza Ladera, Henry (2020)
The objective of the work was to identify genera of filamentous fungi and determine the concentration of lead and zinc in the mining tailings samples. We isolated and identified filamentous fungi using the serial dilution method and the micro culture technique respectively, we also determined heavy metals, pH and% H of tailings samples taken in three representative areas. We identified nine fungal genera: Penicillium, Aspergillus, Paecylomices, Acremonium, Chrysosporium, Trichoderma, Alternaria, Helicosporium and Geoctrichum from a total of sixty-two strains of filamentous fungi present in the mining tailings that had the following physical-chemical characteristics: Zinc (Zn) with 8810.4 ppm and lead (Pb) 3844.4 ppm, the pH had a variation of 1.75 - 7.85 and % H of 10.7 - 2.6.